Incidence of Phlebitis Following the Use of Peripheral IV Line at X Hospital - Margareta Sijabat; Sisilia Desiana Nduru; Ayu Monaretha B; Yenni Ferawati Sitanggang; Elissa Oktoviani Hutasoit (Indonesian Contemporary Nursing Journal, 2021)
Introduction: Intravenous (IV) line infusion therapy is a therapy given to patients who are admitted or having a specific therapy. The IV-line therapy may include fluid therapy, medication administration and blood therapy. Based on the data found in Hospital X, there were 30 incidence of phlebitis in 2017. This study aimed to describe the factors of phlebitis incidence in X hospital. Method: This study was a retrospective study using 50 clinical record of the inpatient patients. The inclusion criteria were all documents of those who are hospitalized at least three days. Result: The result describes three factors following the incidence of phlebitis, such as intrinsic factors, chemical factors, and mechanical factors. The Intrinsic factors included age, gender and medical diagnosis. While Mechanical factors consist of the size of catheter, location and length of infusion. The Chemical factors were of infusion fluid type and infusion rate. Conclusion: The conclusion of this study was the three factors are modifiable factors. Thus, nurses need to assess and evaluate patients’ infusion in order to prevent a higher case of phlebitis. As a recommendation for further study is to analyze the correlation between those factors to the incidence of phlebitis.